The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.3171/jns.1998.88.1.0043
|View full text |Cite
|
Sign up to set email alerts
|

Dose—response tolerance of the visual pathways and cranial nerves of the cavernous sinus to stereotactic radiosurgery

Abstract: The structures of the visual pathways (the optic nerve, chiasm, and tract) exhibit a much higher sensitivity to single-fraction radiation than other cranial nerves, and their particular dose-response characteristics can be defined. In contrast, the oculomotor and trigeminal nerves have a much higher dose tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
185
1
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 482 publications
(201 citation statements)
references
References 42 publications
8
185
1
5
Order By: Relevance
“…Reports from retrospective trials of SRS specifically addressing pituitary macroadenoma show similar results 20,21 , although in one series, macroadenomas tended to have worse local control. Local failures were also more common in cases in which the tumour extended into the cavernous sinus 20 .…”
mentioning
confidence: 52%
“…Reports from retrospective trials of SRS specifically addressing pituitary macroadenoma show similar results 20,21 , although in one series, macroadenomas tended to have worse local control. Local failures were also more common in cases in which the tumour extended into the cavernous sinus 20 .…”
mentioning
confidence: 52%
“…We ensured that the optic nerves or brainstem received no more than 8-10 Gy of radiation. 1,5,8,13) Recent advances of MR angiography have provided less-invasive methods for the identification of AVFs, but cavernous sinus and inferior petrosal sinus flow signals may cause false-positive findings in patients without symptoms or signs of CCF. 3) However, MR angiography is useful for following up patients treated for dural CCF.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, some studies have shown that injury to the optic nerve or chiasm may occur if Ͼ 8-10 Gy is delivered in a single fraction to a segment of the optic apparatus, 13,32 while in another study craniopharyngiomas were successfully treated with a limit of 13 Gy to the optic apparatus. 29 In general, however, radiosurgery is contraindicated if the distance between the tumor and optic apparatus is Ͻ 3 mm because the visual pathways would typically receive Ͼ 10 Gy is these situations.…”
Section: Discussionmentioning
confidence: 99%